Intramolecular-initiating photopolymerization behavior of nanogels with the capability of reducing shrinkage. Issue 45 (4th November 2016) - Han, Junyi; Jiang, Shengling; Gao, Yanjing; Sun, Fang
Abstract : Multifunctional nanogels are successfully synthesized to initiate photopolymerization and to reduce polymerization shrinkage under UV irradiation. Abstract : A series of nanogels possessing both benzophenone and hydrogen-donating groups in the skeleton were synthesized and characterized. The photochemical properties and photoinitiation mechanism of the nanogels were investigated by ultraviolet absorption spectroscopy, real-time infrared spectroscopy, laser flash photolysis and electron spin resonance. The nanogels have a strong absorption characteristic centered at 275 nm. Compared to the bare benzophenone, the nanogels have longer triplet state lifetime that reached up to 1.9 μs. Furthermore, the nanogels can generate both alkyl radicals and amino radicals that can effectively initiate the polymerization of acrylate monomers. More importantly, the nanogels can significantly reduce the volume shrinkage of UV-cured materials and the migration of photolysis fragments. The nanogels should have potential applications for preparing more environmentally friendly materials.